High Strength Al-Alloys: Microstructure, Corrosion and Principles of Protection - Hughes, Anthony E.; Birbilis, Nick; Mol, Johannes M.C.; Garcia, Santiago J.; Zhou, Xiaorong; Thompson, George E. (IntechOpen, 2011)
None